PELAKSANAAN PRESTASI DALAM KEADAAN MEMAKSA YANG TERJADI PADA MASA PANDEMIK - Inri Januar (to-ra, 2020)
Covid 19 virus is becoming a pandemic throughout the world including Indonesia, therefore was born legislation that was deemed necessary to limit activities outside the home in order to reduce the spread of the virus. As a result, many debtors cannot carry out their obligations on the grounds of forced conditions. Forceful situation due to the existence of laws and regulations is the reason for the non implementation of debtor obligations, this is justified according to law. To be determined in a forceful condition other than an agreement, the court can provide its judgment. Key word: Pandemic, Overmacht, Regulation.